anonymous
  • anonymous
help.... a uniformly accelerating train passes a person on the ground.If the speeds of the points 1, 2 & 3 on the train as they pass the person are u1, u2 & u3 respectively and u1/u2 = u2/u3, then s1/s2 is (where s1 is the distance between 1 & 2 ; s2 between 2 & 3 respectively) a. s1/s2 = u2/u3 b. s1/s2 =(u1/u2)^2 pls tell me how 2 do this....
Physics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Consider the Newton's third equation of motion: v^2+u^2=2as, where "v" denotes final velocity, and "u" denotes initial velocity. Here, acceleration is uniform, therefore, "2a" is constant. Hence, v^2-u^2 is proportional to "s"......(i) Consider the first case. Here, "u2" is the final velocity, "u1" is the initial velocity and "s1" is the distance between the points "1" and "2". Therefore, (u2)^2-(u1)^2=s1.....(ii) But given that u1/u2=u2/u3, or (u2)^2=u1u3 Hence, by substitution, we get equation(ii) as follows: u1u3-(u1)^2=s1 Or, u1(u3-u1)=s1..........(iii) Consider the second case. Here, (u2) is the initial velocity, and (u3) is the final velocity, and "s2" is the distance between points "2" and "3". So, we get, (u3)^2-(u2)^2=s2 But we know that (u2)^2=u1u3 Therefore, (u3)^2- u1u3=s2 Or, u3(u3-u1)=s2 Now, on solving, we get, s1/s2=[u1(u3-u1)]/[u3(u3-u1)]=u1/u3 We know that u1u3=(u2)^2 Or, (u1u3)/(u3u2)=(u2*u2)/(u3u2) Or, (u1/u3)(u3/u2)=u2/u3 Or, u1/u2=u2/u3 Therefore, the answer = u2/u3
anonymous
  • anonymous
thank u...! :)
anonymous
  • anonymous
I don't get the last step.

Looking for something else?

Not the answer you are looking for? Search for more explanations.